Potential biomarkers for testicular germ cell tumour: Risk assessment, diagnostic, prognostic and monitoring of recurrence. (3rd February 2021) - Lakpour, Niknam; Saliminejad, Kioomars; Ghods, Roya; Reza Sadeghi, Mohammad; Pilatz, Adrian; Khosravi, Farhad; Madjd, Zahra
Abstract: Testicular germ cell tumour (TGCT) is considered a relatively rare malignancy usually occurring in young men between 15 and 35 years of age, and both genetic and environmental factors contribute to its development. The majority of patients are diagnosed in an early‐stage of TGCTs with an elevated 5‐year survival rate after therapy. However, approximately 25% of patients show an incomplete response to chemotherapy or tumours relapse. The current therapies are accompanied by several adverse effects, including infertility. Aside from classical serum biomarker, many studies reported novel biomarkers for TGCTs, but without proper validation. Cancer cells share many similarities with embryonic stem cells (ESCs), and since ESC genes are not transcribed in most adult tissues, they could be considered ideal candidate targets for cancer‐specific diagnosis and treatment. Added to this, several microRNAs (miRNA) including miRNA‐371‐3p can be further investigated as a molecular biomarker for diagnosis and monitoring of TGCTs. In this review, we will illustrate the findings of recent investigations in novel TGCTs biomarkers applicable for risk assessment, screening, diagnosis, prognosis, prediction and monitoring of the relapse.